“Go with the Flo”: Conducting rapid research on prenatal stress following Hurricane Florence as participant observers - Howells, Michaela; Dancause, Kelsey (Frontiers in Sociology, 2022)
In this article, we explore the challenges of conceptualizing, designing, and establishing a rapid research agenda as a local researcher following a disaster. We share what we learned while developing and implementing this rapid study and explore the challenges shaped by time pressures, our local context, and resource availability. We identify four core challenges, experienced conducting rapid research, and provide suggestions to overcome these challenges. Our goal is to provide insight to undergraduates, graduate students, and professionals who are considering rapid research inside or outside their own communities.